From prostate‐specific antigen (PSA) to precursor PSA (proPSA) isoforms: a review of the emerging role of proPSAs in the detection and management of early prostate cancer. (3rd July 2012) - Hori, Satoshi; Blanchet, Jean‐Sebastien; McLoughlin, John
What's known on the subject? and What does the study add?: Despite the popularity of PSA blood testing for prostate cancer, there are a number of important limitations of this popular serum marker including the limited ability to accurately distinguish patients with and without prostate cancer and those who harbour an aggressive form of the disease. This is especially true when the total PSA is <10 ng/mL. Thus, significant efforts have been placed to find new serum markers that can help overcome these limitations. In this review article, we discuss the emerging role of the various precursor forms of PSA (proPSAs), with a special emphasis on [‐2]proPSA in the detecion and management of early prostate cancer. The clinical utility of Prostate Health Index ( phi ) is also discussed. Despite the overall success of prostate‐specific antigen (PSA) blood test, its use as a serum marker for prostate cancer has been limited due to the lack of specificity, especially in men presenting with a total PSA (tPSA) level of <10 ng/mL. PSA testing has also resulted in an increase in the number of patients being diagnosed with low‐grade, potentially clinically insignificant prostate cancer. There is therefore an urgent need for new markers that can accurately detect as well as differentiate patients with aggressive vs unaggressive prostate cancer. In this review, we discuss the emerging role of precursor forms of PSA (proPSAs) and the Prostate Health Index ( phi ) measurement in the detection and management of early stage prostate cancer. A literature search was conducted using PubMed® to identify key studies. Studies to date suggest that [‐2]proPSA, a truncated form of proPSA is the most cancer‐specific form of all, being preferentially expressed in cancerous prostatic epithelium and being significantly elevated in serum of men with prostate cancer. There is evidence to suggest that %[‐2]proPSA measurement ([‐2]proPSA/free PSA [fPSA] × 100) improves the specificity of both tPSA and fPSA in detecting prostate cancer. phi incorporating [‐2]proPSA, fPSA and tPSA measurements has also yielded promising results and appears superior to tPSA and fPSA in predicting those patients with prostate cancer. Increased phi levels also seem to preferentially detect patients harbouring more aggressive disease. Further studies in the form of large, multicentre, prospective trials with detailed health economic analyses are required to evaluate the true clinical applicability of these novel markers.